Rational Expectations and the Firm's Dividend Behavior - Nakamura, Alice; Nakamura, Masao (The Review of Economics and Statistics, 1985)
In Lintner's model of dividend behavior of firms change in dividends is a function of current earnings and lagged dividends. We show that under a rational expectations hypothesis of management behavior change-individends equation should include lagged earnings as an additional explanatory variable, and that expected sign of coefficient of lagged earnings variable is positive. Fama and Babiak predicted opposite sign for a lagged earnings variable in such an equation. Estimation and simulation results based on panel data for U.S. and Japanese firms provide modest econometric support for our Rational model. A good descriptive model of firms' dividend policies is useful, for example, for portfolio managers and for studying aspects of firm behavior such as interactions between investment and financing decisions and the management's transmissions of signals concerning changes in expected future earnings.' The econometric specifications of dividend behavior favored in literature are Lintner model (Lintner (1956)) and its FamaBabiak (FB) variant (Fama and Babiak (1968)). In Lintner model change in dividends is regressed on current earnings and lagged dividends. Fama and Babiak (1968) note that forecasting ability of Lintner's model is increased by adding lagged earnings as a regressor. We show that under a rational expectations hypothesis dividend behavior of firms may be described by an extension of Lintner's model, that we call Rational model, that includes lagged earnings as an additional explanatory variable. An important empirical difference between our Rational model and FB model is that expected sign of coefficient of lagged earnings variable is negative in Rational model while in FB model it is implied to be positive (see Fama and Babiak (1968, equation 10)). Our results based on panel data for U.S. and Japanese firms provide modest support for Rational model.2 I. The Rational Model of Dividend Behavior Our point of departure is partial adjustment model of dividend behavior of a firm (Lintner (1956)) given by AD, = aO + c(D,* D,-) + u,; t= 1,2,...,T (1) where A Dt = Dt -Dtdenotes change in dividends, Dt is dividends paid out in time period (year) t, Dt* is unobserved target dividend payout, c is speed of adjustment to difference between target dividend payout and last year's payout, ao is a constant and ut is an error term often assumed to be independently and normally distributed with zero mean over time periods. In Lintner model target dividend payout is replaced by Dt* = ryt which means that desired dividend payout is a fraction r of current earnings (yt). Thus Lintner's model is A Dt= a0 + cryt cDt+ Ut. (2) This model fits U.S. data (at both aggregate and disaggregate levels) quite well. Suppose instead that management determines target dividend payout by